2009
DOI: 10.1007/s10295-009-0583-2
|View full text |Cite
|
Sign up to set email alerts
|

Selective activity of Mucor plumbeus reductase towards (−)-camphorquinone

Abstract: The biotransformation of 1R-(-)-camphorquinone, achieved by growing cells of four fungi species isolated from soil (Mucor plumbeus, Lecanicillium muscarium, Thamnostylum sp. and Syncephalastrum racemosum), was investigated in optimized culture media for each species. Fungi were grown aerobically under shaking and their activities with respect to camphorquinone were monitored for 20 days by gas chromatography coupled to mass spectrometry (GCMS). Camphorquinone was found to be stable in control flasks throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The NMR technique is known as very useful to experimental characterization of organic compounds; an example was shown recently for the camphorquinone biotransformation products. 10 In this work the gauge-independent atomic orbital (GIAO) method 11 was applied for the calculation of the 13 C and 1 H magnetic shielding constants (σ) and the chemical shift (δ) for selected atoms obtained on the δ-scale relative to the TMS at the B3LYP/6-311+G(2d,p) level, as previously described in the anhydrotetracycline-platinum dichloride complex study reported by our group. 12 The solvent effect on the calculation of chemical shifts was also evaluated using a polarizable continuum model (PCM), 13 followed by 13 C NMR calculations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The NMR technique is known as very useful to experimental characterization of organic compounds; an example was shown recently for the camphorquinone biotransformation products. 10 In this work the gauge-independent atomic orbital (GIAO) method 11 was applied for the calculation of the 13 C and 1 H magnetic shielding constants (σ) and the chemical shift (δ) for selected atoms obtained on the δ-scale relative to the TMS at the B3LYP/6-311+G(2d,p) level, as previously described in the anhydrotetracycline-platinum dichloride complex study reported by our group. 12 The solvent effect on the calculation of chemical shifts was also evaluated using a polarizable continuum model (PCM), 13 followed by 13 C NMR calculations.…”
mentioning
confidence: 99%
“…Harmonic frequency calculations were performed for the characterization of each structure as true minima (all frequencies are real), which also yield directly the IR spectra (vibrational frequencies and intensities of normal modes). The NMR technique is known as very useful to experimental characterization of organic compounds; an example was shown recently for the camphorquinone biotransformation products . In this work the gauge-independent atomic orbital (GIAO) method was applied for the calculation of the 13 C and 1 H magnetic shielding constants (σ) and the chemical shift (δ) for selected atoms obtained on the δ-scale relative to the TMS at the B3LYP/6-311+G(2d,p) level, as previously described in the anhydrotetracycline−platinum dichloride complex study reported by our group .…”
mentioning
confidence: 99%
“…1). The activity of this fungus was stereoselective with respect to camphorquinone, a feature that can be further exploited for synthetic purposes (Souza et al 2009).…”
Section: Biotransformation Of Monoterpenoidsmentioning
confidence: 98%
“…They are the subject of many research projects owing to their importance in regulating metabolism in both plants and animals. Biotransformation has been extensively used to carry out stereo-and regioespecific modifications of naturally occurring monoterpenes in order to either enhance their biological activity or to prepare building blocks and enantiomerically pure derivatives that can be used as intermediate molecules in the synthesis of more complex compounds (Souza et al 2009). For example, in 2009 Esmaeili et al reported on (-)-menthol biotransformation by Mucor ramannianus obtaining several interesting structures such as sabinane or 1,8-cineole, in high yields (Esmaeili et al 2009).…”
Section: Biotransformation Of Monoterpenoidsmentioning
confidence: 99%
“…There are several reports on the biotransformation of 1 by microorganisms, cultured plant cells, and cyanobacteria, for example, Absidia orchidis (Pfrander & Tamm 1969), Acinetobacter sp. (Rebolledo et al 1991), A. niger , Fusarium solani , Mucor mucedo , Rhizoctonia solani , Glomerella cingulata (Miyazawa et al 1995;Miyazawa et al 1997), M. plumbeus (Souza et al 2009), Catharanthus roseus , Nicotiana tabacum (Chai et al 2001), Synechococcus elongatus and Synechocystis sp. (Utsukihara et al 2004).…”
Section: Introductionmentioning
confidence: 99%